A uber‐airbnb mixture flexibility peer‐to‐peer market in integrated TSO‐DSO architecture. Issue 1 (24th June 2022) - Shan, Lanqing; Gu, Chenghong; Li, Furong
Abstract: With the launch of global decarbonisation, the infiltration of low‐carbon distributed energy resources (DERs) is increasing. The future transaction platforms for those flexibilities are considered to be peer‐to‐peer (P2P) ones conforming to resources' characteristics of small‐scale and independence. This research reviews current flexibility‐related topics and proposes one P2P flexibility market filling in the gaps. The contribution of this research includes: (1) it constructs a flexibility market combining pricing strategy and matching strategy of the mature and successful real‐world P2P business models, accommodating the penetration of DERs. The proposed automatic trading market could mobilise the enthusiasm of market participants and satisfy individuals' needs for a convenient market. (2) it proposes a dynamic pricing strategy where prices fluctuate with the features and portfolios of market participants. More adequate market signals are provided with the promotion of market equity. (3) it discusses the segmentation tendency of the flexibility market when considering energy products as pure commodities following the disintegration from the transmission system operator to the distribution system operator. The feasibility of the proposed market under future energy scenarios is thus explored.